SENP1-mediated NEMO deSUMOylation in adipocytes limits inflammatory responses and type-1 diabetes progression - Lan Shao; Huanjiao Jenny Zhou; Haifeng Zhang; Lingfeng Qin; John Hwa; Zhong Yun; Weidong Ji; Wang Min (Nature Communications)
Abstract Adipocyte dysfunction correlates with the development of diabetes. Here we show that mice with a adipocyte-specific deletion of the SUMO-specific protease SENP1 gene develop symptoms of type-1 diabetes mellitus (T1DM), including hyperglycaemia and glucose intolerance with mild insulin resistance. Peri-pancreatic adipocytes from SENP1-deficient mice exhibit heightened NF-κB activity and production of proinflammatory cytokines, which induce CCL5 expression in adjacent pancreatic islets and direct cytotoxic effects on pancreatic islets. Mechanistic studies show that SENP1 deletion in adipocytes enhances SUMOylation of the NF-κB essential molecule, NEMO, at lysine 277/309, leading to increased NF-κB activity, cytokine production and pancreatic inflammation. We further show that NF-κB inhibitors could inhibit pre-diabetic cytokine production, β-cell damages and ameliorate the T1DM phenotype in SENP1-deficient mice. Feeding a high-fat diet augments both type-1 and type-2 diabetes phenotypes in SENP1-deficient mice, consistent with the effects on adipocyte-derived NF-κB and cytokine signalling. Our study reveals previously unrecognized mechanism regulating the onset and progression of T1DM associated with adipocyte dysfunction.